HUBUNGAN ASUPAN ZAT BESI DENGAN KEJADIAN ANEMIA PADA REMAJA PUTRI SMU 98 di JAKARTA TIMUR - Junengsih Junengsih; Yuliasari Yuliasari (Poltekkes Kemenkes Jakarta III, 2017)
In Indonesia iron deficiency anemia in adolescent girls is still a major problem, due to the rapid growth of adolescents and an imbalance between nutritional intake and the activities of adolescents. Efforts to prevent and improve nutrition should be done immediately because it can cause impacts, among others, lower adolescent endurance so easily affected by disease, decreased ability and concentration of learning, decreased fitness and learning achievement. This study aims to determine the relationship between nutritional status and nutritional intake with the incidence of anemia in young women in SMU 98 Jakarta Year 2016. This research type is analytical with cross sectional approach. The sample of this research are students X, XII and XII. 200 students at SMU 98 Jakarta Timur in August 2017. Sampling is done by stratified random sampling and taken proportionally. Data collection with IMT examination, consumption with recall form and Hb level measurement with Hemocue tool. Data analysis using chi square test. The results obtained iron intake can reduce the chances of anemia in young women. Teenagers who get less iron intake, 7.1 times more risky to experience anemia than teenagers who get iron intake well after controlled by variable menstrual patterns, physical activity and breakfast habits. Recommendations for young women to increase iron intake and balanced diet.